2021
DOI: 10.1371/journal.pone.0260475
|View full text |Cite
|
Sign up to set email alerts
|

Views and experiences of compassion in Sri Lankan students: An exploratory qualitative study

Abstract: Practicing compassion has shown to reduce distress and increase emotional well-being in clinical and non-clinical populations. The existing research is primarily focused on Western populations although the concepts of compassion are heavily influenced by Asian Buddhist views. There is a dearth of compassion research conducted particularly in the Asian context. Therefore, this study aimed to explore the views and lived experiences of compassion in Sri Lankan students, to understand whether compassion is a socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Thus, a plausible explanation of fear of self-compassion predicting higher compassion towards others in the Sri Lankan group may be that, despite the fear of treating themselves with compassion, they may have felt compelled to offer it to others, to avoid social rejection. Previous studies identified that some Sri Lankans offer compassion to others, out of obligatory and submissive reasons (Kariyawasam et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a plausible explanation of fear of self-compassion predicting higher compassion towards others in the Sri Lankan group may be that, despite the fear of treating themselves with compassion, they may have felt compelled to offer it to others, to avoid social rejection. Previous studies identified that some Sri Lankans offer compassion to others, out of obligatory and submissive reasons (Kariyawasam et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, however, Thai participants (a Buddhist-influenced culture) were more self-compassionate than the American and Taiwanese participants. The collectivistic social dynamic in cultures such as Sri Lanka is found to inhibit people from receiving compassion from themselves and others (Montero-Marin et al ., 2018 ; Steindl et al ., 2020 ; Kariyawasam et al ., 2021 ), due to eastern cultural norms discouraging help-seeking behaviour, as seeking help is considered as a failure that brings shame to one and those around oneself (Kee, 2004 ). Thus, it seems fair to propose that whilst the Buddhist religion encourages compassion, the collectivistic cultural dynamic may be a factor that inhibits people's compassionate experiences.…”
Section: Compassion Across Culturesmentioning
confidence: 99%
“…Therefore, it seems fair to propose that the CEAS may be a more appropriate measure of compassion. However, none of the papers included in this meta-analysis used the CEAS, although other recent research using this measure in Asian countries such as Japan (Asano et al, 2020) and Sri Lanka (Kariyawasam et al, 2021(Kariyawasam et al, , 2022 have emphasised the advantages of using this measure (Asano et al, 2020). Thus, it would be useful for future research to investigate the effectiveness of compassion-based interventions using the CEAS in Asian communities to further understand the interplay between the three flows of compassion and well-being.…”
Section: Discussion Compassion-based Interventions On Self-compassionmentioning
confidence: 99%
“…Overall, this review highlights that the lack of research exploring the effectiveness of compassionbased interventions in Eastern cultures, as there were only three Asian countries that have researched this area so far. This was surprising given that many Asian countries such as Sri Lanka are familiar with compassion practice due to the significant Buddhist influence in such cultures (Kariyawasam et al, 2021(Kariyawasam et al, , 2022.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…For example, its evolutionary origins, its neurobiological substrates and its relations with emotional and behavioral domains such as love, reconciliation, or cooperation ( Goetz et al, 2010 ; Kim et al, 2020 ; Novak et al, 2022 ). Social and psychosocial perspectives have also contributed to understanding the phenomenology behind compassion and the sociocultural properties that influence variations in conceptual understanding and/or behavioral expressions ( Keltner et al, 2010 ; Kariyawasam et al, 2021 ). As reasoned from the previous lines, compassion implies empathic abilities that allow inferring the suffering of others, as well as judgments, evaluation of social signals and decision making to perform helping behaviors.…”
Section: Introductionmentioning
confidence: 99%